Endothelial NOD1 directs myeloid cell recruitment in atherosclerosis through VCAM‐1. Issue 3 (29th November 2018) - González-Ramos, Silvia; Paz-García, Marta; Rius, Cristina; del Monte-Monge, Alberto; Rodríguez, Cristina; Fernández-García, Victoria; Andrés, Vicente; Martínez-González, José; Lasunción, Miguel A.; Martín-Sanz, Paloma; Soehnlein, Oliver; Boscá, Lisardo
ABSTRACT: Atherosclerosis is a chronic disease characterized by vascular lipid retention and inflammation, and pattern recognition receptors (PRRs) are important contributors in early stages of the disease. Given the implication of the intracellular PRR nucleotide‐binding oligomerization domain 1 (NOD1) in cardiovascular diseases, we investigated its contribution to early atherosclerosis. We evidenced NOD1 induction in atherosclerotic human and mouse tissues, predominantly in vascular endothelial cells. Accordingly, NOD1 genetic inactivation in Apoe −/− mice reduced not only atherosclerosis burden, but also monocyte and neutrophil accumulation in atheromata. Of note, in the presence of either peptidoglycan or oxidized LDLs, endothelial NOD1 triggered VCAM‐1 up‐regulation through the RIP2‐NF‐κB axis in an autocrine manner, enhancing firm adhesion of both sets of myeloid cells to the inflamed micro‐ and macro vasculature in vivo . Our data define a major proatherogenic role for endothelial NOD1 in early leukocyte recruitment to the athero‐prone vasculature, thus introducing NOD1 as an innovative therapeutic target and potential prognostic molecule.—González‐Ramos, S., Paz‐García, M., Rius, C., del Monte‐Monge, A., Rodríguez, C., Fernández‐García, V., Andrés, V., Martínez‐González, J., Lasunción, M. A., Martín‐Sanz, P., Soehnlein, O., Boscá, L. Endothelial NOD1 directs myeloid cell recruitment in atherosclerosis through VCAM‐1. FASEB J. 33, 3912–3921 (2019). www.fasebj.org